Should the EC abandon article 81 (3) EC? - Kristoffersen, Joakim Aakre (Universitetet i Tromsø, 2008)
Denne masteroppgaven er avlagt ved Swansea University, men inngår i graden ved Universitetet i Tromsø. Den korrekte tolkningen av artikkel 81 er uklar grunnet nyere rettspraksis. Det kan blant annet argumenteres med at artikkel 81 (3) er blitt overflødig på grunn av oppveiingen av positive og negative konkurranse vilkår under artikkel 81 (1). Oppgaven vurderte ikke bare hvordan rettstilstanden er i dag, men også hvordan artikkel 81 burde utformes. In EC competition law the introduction of an economic approach can be observed in the Community case-law and decisions and notices published by the EC Commission. This has consequently affected both on the substantive and procedural content of EC competition law. The purpose of this dissertation is to examine how this development has influenced the content of article 81 (1) and whether the role of article 81 (3) has become surplus to requirements. This analysis is divided in three chapters. First, it looks at the economic debate behind EC competition law and the changing policy aims. Secondly, it discusses whether the EC courts have adopted the American rule of reason doctrine and what consequences this has for the function of article 81 (3). Lastly it considers whether article 81 should be modified. The analysis is based on the examination of the CFI’s and the ECJ’s published decisions, EC regulations and notices and relevant academic literature.